SERVING UKRAINIAN CULTURE AND ART - HRYTSAN, ANATOLII (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
The article highlights the main achievements of the Educational and Scientific Institute of Arts of Vasyl Stefanyk Precarpathian National University in educational, scientific, artistic and performative spheres.